Kingdom of beauty : mingei and the politics of folk art in Imperial Japan - Brandt, Kim (Asia-Pacific., 2007)
A Study of the Weatherhead East Asian Institute, Columbia UniversityKingdom of Beauty shows that the discovery of mingei (folk art) by Japanese intellectuals in the 1920s and 1930s was central to the complex process by which Japan became both a modern nation and an imperial world power. Kim Brandt's account of the mingei movement locates its origins in colonial Korea, where middle-class Japanese artists and collectors discovered that imperialism offered them special opportunities to amass art objects and gain social, cultural, and even political influence. Later, min.